Outcomes after surgery in patients with and without recent influenza: a nationwide population-based study - Lam, Fai; Liao, Chien-Chang; Chen, Ta-Liang; Huang, Yu-Min; Lee, Yuarn-Jang; Chiou, Hung-Yi (Frontiers in Medicine, 2023)
Background The influence of recent influenza infection on perioperative outcomes is not completely understood. Method Using Taiwan’s National Health Insurance Research Data from 2008 to 2013, we conducted a surgical cohort study, which included 20,544 matched patients with a recent history of influenza and 10,272 matched patients without. The main outcomes were postoperative complications and mortality. We calculated odds ratios (ORs) and 95% confidence intervals (CIs) for the complications and for mortality in patients with a history of influenza within 1–14 days or 15–30 days compared with non-influenza controls. Results Compared with patients who had no influenza, patients with influenza within preoperative days 1–7 had increased risks of postoperative pneumonia (OR 2.22, 95% CI 1.81–2.73), septicemia (OR 1.98, 95% CI 1.70–2.31), acute renal failure (OR 2.10, 95% CI 1.47–3.00), and urinary tract infection (OR 1.45, 95% CI 1.23–1.70). An increased risk of intensive care admission, prolonged length of stay, and higher medical expenditure was noted in patients with history of influenza within 1–14 days. Conclusion We found that there was an association between influenza within 14 days preoperatively and the increased risk of postoperative complications, particularly with the occurrence of influenza within 7 days prior to surgery.